Testing for the economic and environmental impacts of EU Emissions Trading System: A panel GMM approach - Gretszel, Piotr; Gurgul, Henryk; Lach, Lukasz; Schleicher, Stefan (Managerial Economics, 2021)
The COVID‑19 pandemic has had a great impact on the economies of the EU, also with regard to the future of EU climate policy. The plan to rebuild and support the EU economy seems to place less emphasis on environmental issues as the main focus has been shifted to a quick economic recovery. One of the issues discussed in this context is the continued operation of the EU ETS. From this perspective, empirical research devoted to a thorough analysis of the impact of the EU ETS is of particular importance. At the same time, the current economic literature lacks any econometric analyzes devoted to the issues in question that would use detailed and reliable databases on EU ETS like the one provided by the Wegener Center for Climate and Global Change. The aim of this paper is to make a preliminary assessment of the effectiveness of the EU ETS in terms of reducing the actual emissions while preserving the economic growth of EU member states. The extensive empirical analysis is focused on examining the issues in question for different phases of the EU ETS and various groups of EU economies that vary in terms of economic development and the overall air pollutant emission.